Viral vector-mediated selective and reversible blockade of the pathway for visual orienting in mice - Isa, Tadashi; Sooksawate, Thongchai; Isa, Kaoru; Matsui, Ryosuke; Kato, Shigeki; Kinoshita, Masaharu; Kobayashi, Kenta; Watanabe, Dai; Kobayashi, Kazuto (Frontiers in Neural Circuits, 2013)
Recently, by using a combination of two viral vectors, we developed a technique for pathway-selective and reversible synaptic transmission blockade, and successfully induced a behavioral deficit of dexterous hand movements in macaque monkeys by affecting a population of spinal interneurons. To explore the capacity of this technique to work in other pathways and species, and to obtain fundamental methodological information, we tried to block the crossed tecto-reticular pathway, which is known to control orienting responses to visual targets, in mice. A neuron-specific retrograde gene transfer vector with the gene encoding enhanced tetanus neurotoxin (eTeNT) tagged with enhanced green fluorescent protein (EGFP) under the control of a tetracycline responsive element was injected into the left medial pontine reticular formation. 7–17 days later, an adeno-associated viral vector with a highly efficient Tet-ON sequence, rtTAV16, was injected into the right superior colliculus. 5–9 weeks later, the daily administration of doxycycline (Dox) was initiated. Visual orienting responses toward the left side were impaired 1 - 4 days after Dox administration. Anti-GFP immunohistochemistry revealed that a number of neurons in the intermediate and deep layers of the right superior colliculus were positively stained, indicating eTeNT expression. After the termination of Dox administration, the anti-GFP staining returned to the baseline level within 28 days. A second round of Dox administration, starting from 28 days after the termination of the first Dox administration, resulted in the reappearance of the behavioral impairment. These findings showed that pathway-selective and reversible blockade of synaptic transmission causes behavioral effects also in rodents, and that the crossed tecto-reticular pathway surely controls visual orienting behaviors.